Optional and non-optional teacher competencies from aspects of content knowledge in vocational college - Rubani, Siti Nur Kamariah; Norbashahul, Dzulkarnain Hakim; Ariffin, Arihasnida; Zakaria, Normah; Hamzah, Norhasyimah (2021)
The purpose of the study was to identify the competency of option teachers and non-option teachers in terms of knowledge at two vocational colleges of Chenor Agriculture Vocational College and Teluk Intan Agriculture Vocational College. A total of 88 respondents were selected for the study comprising various fields of agriculture. Questionnaire forms were used as an instrument for the study. The data was analyzed using mean values and. The Mann Whitney test was used to identify the difference between the teacher choice and teacher competence in the context of content knowledge. The results showed that the teachers' competence in content knowledge was at a high level with a mean value of 3.04. While the findings of the Mann-Whitney U test supported the suggestion that Option and non-option teacher groups have different levels of content knowledge.